Molecular dynamics approach in designing Thermostable Bacillus circulans Xylanase - Noorbatcha, Ibrahim Ali; Mohd. Salleh, Hamzah (2011)
We have applied molecular dynamics methods as a tool in designing thermostable Bacillus circulans Xylanase, by examining Root Mean Square Deviation (RMSD) of enzymes structure at its optimum temperature and compare with its high temperature behavior. As RMSD represents structural fluctuation at a particular temperature, a better understanding of this factor will suggest approaches to bioengineer these enzymes to enhance their thermostability. In this work molecular dynamic simulations of Bacillus circulans xylanase (BcX) have been carried at 318K (optimum catalytic temperature) and 343K (BcX reported inactive temperature). Structural analysis revealed that the fluctuations of the β-sheet regions are larger at higher temperatures compared to the fluctuations at optimum temperature.